ผลของการกล้าแสดงออกอย่างเหมาะสมและอารมณ์ต่อการคล้อยตามสิ่งชี้นำในกระบวนการซักถาม - ภารดี ศิริสุทธิพัฒนา (จุฬาลงกรณ์มหาวิทยาลัย, 2007)
The purpose of this study was to examine the effects of assertiveness and emotion on interrogative suggestibility. One hundred and twenty undergraduate students, 45 males and 75 females, were asked to complete assertiveness questionnaire, see the emotional pictures, and write about their past experience to induce the emotion according to the conditions. Immediately after this, they participated in the interrogative suggestibility procedure which comprises listening to a story, answering to the leading questions, receiving the negative feedback and answering to the repeated leading questions. The procedure results in yield 1, yield 2, shift, and total suggestibility scores (Gudjonsson, 1997). Results show that: 1.There is no significant difference between negative and positive emotion on yield 1 and total suggestibility. 2.Participants who are low in assertiveness are significantly higher yield 1 and total suggestibility than participants who are high in assertiveness (p < .001). 3.For the low assertiveness condition, there is no significant difference between the negative emotion group and the positive emotion group on yield 1 and total suggestibility. 4.There is no significant interaction between assertiveness and emotion on yield 1; however, there is a significant interaction between assertiveness and emotion on total suggestibility (p < .05).